Efficient Interconnection in Perovskite Tandem Solar Cells. Issue 7 (16th April 2020) - Li, Can; Wang, Yong; Choy, Wallace C. H.
Abstract: Organic–inorganic hybrid perovskite materials are excellent candidates as light absorbers in tandem solar cells with advantages of tunable bandgaps, high absorption coefficients, facile fabrication processes, and low costs. Tandem devices offer a route to further improve the efficiency and reduce the cost for the solar cell practical applications. One critical challenge that limits the development of two‐terminal perovskite‐based tandem devices is the interconnection between two subcells. To achieve efficient interconnection in the tandem devices, it is required to simultaneously fulfill the high electrical, optical, and chemical requirements. In particular, chemical protection requirement is necessary to enable a tandem device in the case of solution‐processed perovskite–perovskite tandem solar cells. In this work, recent advances of interconnection in perovskite‐based two‐terminal tandem solar cells are reviewed. A brief introduction to the topic is first given. The definition, functions, and requirements of interconnecting layers in two‐terminal tandem devices are then discussed. Next, the insights into recent advances of interconnecting layers in two‐terminal perovskite‐based tandem solar cells (perovskite–perovskite, perovskite–polymer, perovskite–inorganic tandem solar cells) are further described. Finally, an outlook of the future research directions and a brief summary are drawn. Abstract : Efficient and robust interconnection in perovskite‐based tandem solar cells is necessary to ensure high performances. This review summarizes the functions, requirements, and recent advances of interconnecting layers in perovskite‐based tandem solar cells.